2015
DOI: 10.3233/jpd-150557
|View full text |Cite
|
Sign up to set email alerts
|

Linking Smoking, Coffee, Urate, and Parkinson’s Disease – A Role for Gut Microbiota?

Abstract: Abstract. While the etiology and pathogenesis of Parkinson's disease (PD) is still obscure, there is evidence for lifestyle factors influencing disease risk. Best established are the inverse associations with smoking and coffee consumption. In other contexts there is evidence that health effects of lifestyle factors may depend on gut microbiome composition. Considering the gastrointestinal involvement in PD, it was recently speculated, that the associations between smoking, coffee, and PD risk could be mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 78 publications
(102 reference statements)
0
55
0
Order By: Relevance
“…Specifically, both smoking and drinking coffee are associated with significantly reduced incidence of PD, and it has been proposed that protective effects of tobacco and coffee may be mediated at least in part by modulation of the microbiota. 92,102 Some evidence now suggests that changes in certain bacterial taxa that are observed with smoking and coffee consumption resemble the microbiota differences reported in controls compared to PD cases. 102 This raises the possibility that some states of the microbiome may be protective with regard to PD, but it is also possible that the smoking and coffee-associated microbial compositions reflect changes in the intestinal environment or function.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Specifically, both smoking and drinking coffee are associated with significantly reduced incidence of PD, and it has been proposed that protective effects of tobacco and coffee may be mediated at least in part by modulation of the microbiota. 92,102 Some evidence now suggests that changes in certain bacterial taxa that are observed with smoking and coffee consumption resemble the microbiota differences reported in controls compared to PD cases. 102 This raises the possibility that some states of the microbiome may be protective with regard to PD, but it is also possible that the smoking and coffee-associated microbial compositions reflect changes in the intestinal environment or function.…”
Section: Introductionmentioning
confidence: 95%
“…92,102 Some evidence now suggests that changes in certain bacterial taxa that are observed with smoking and coffee consumption resemble the microbiota differences reported in controls compared to PD cases. 102 This raises the possibility that some states of the microbiome may be protective with regard to PD, but it is also possible that the smoking and coffee-associated microbial compositions reflect changes in the intestinal environment or function. Nicotine has well-established anti-inflammatory properties, and coffee increases gut motility, 102 both of which may contribute to an intestinal environment that is resistant to PD-associated pathology.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, a epidemiological study on a large Danish cohort reported a controversial finding describing a significantly reduced future PD risk in patients who underwent truncal vagotomy as a treatment for peptic ulcer in 1977–1995 (55). Recently, it was speculated that changes in gut microbiome (56,57), e.g. as a consequence of smoking or coffee (known modifiers of PD risk), could reduce the likelihood of inflammatory events that might trigger α-synuclein misfolding in the gut wall (58,59).…”
Section: Braak Neuropathological Staging Supports the Concept Of Propmentioning
confidence: 99%
“…Finally, the involvement of the human gut microbiome and PD (56)(57)(58)(59)(60) is an exciting emergent area of research. It is possible that larger particles such as PM 10 , PM 2.5 and PM 2.5−10 , although being too large to cross the blood-brain barrier, could still enter the body via another route.…”
Section: Interactions With Other Environmental Factors Gene-environmmentioning
confidence: 99%